Motivational factors and performance in soccer - Maria Cristina Chimelo Paim (Journal of Physical Education (Maringá), 2008)
This study aimed to verify what were the motivational factors that made teenagers to choose ADUFSM soccer school, and to verify the difference among the groups, the performance and gain scores at soccer basis. The sample comprised 32 persons, 10 to 16 years old, that practice soccer at ADUFSM. The sample was divided in four groups. The motivational factors inventory (MFI) was applied in the beginning of the semester. It was verified, through descriptive statistics, that the stronger motivation for the subjects involvement with soccer was to develop skills (78%), followed by excitation and challenge (72%); affiliation (70%) and aptitude (68%). The performance level evaluation in three different phases was done through soccer basis analytical matrix (SBAM), always in game situation. Five observations per subject were made for each base listed in SBAM, and the execution mistakes were identifies. Initially, an ANOVA was used to deal with the data; later, a post-hoc test. The results showed that learning occurred and that there was a significant difference favoring GF10 in the learning gain scores after the treatment.